Phase-coherent transport in trigonal gallium nitride nanowires. (30th December 2020) - Park, Tae-Eon; Min, Byoung-Chul; Lee, Jaejun; Jeon, Jeehoon; Lee, Ki-Young; Choi, Heon-Jin; Chang, Joonyeon
Abstract: Gallium nitride nanowires (GaN NWs) with triangular cross-section exhibit universal conductance fluctuations (UCF) originating from the quantum interference of electron wave functions in the NWs. The amplitude of UCF is inversely proportional to the applied bias current. The bias dependence of UCF, combined with temperature dependence of the resistance suggests that phase coherent transport dominates over normal transport in GaN NWs. A unique temperature dependence of phase-coherent length and fluctuation amplitude is associated with inelastic electron–electron scattering in NWs. The phase-coherence length extracted from the UCF is as large as 400 nm at 1.8 K, and gradually decreases as temperature increases up to 60 K.